High-leveling water-based oil polish and preparation process thereof

Through the hydrosilicon addition reaction of modified nano-calcium carbonate and silicone, combined with epoxy ring-opening reaction, double-bonded nano-calcium carbonate is formed, which solves the problems of poor leveling performance, low gloss and insufficient wear resistance of acrylate aqueous lacquer, and significantly improves its leveling and wear resistance.

CN119553536AActive Publication Date: 2025-03-04红河雄风印业有限责任公司
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411913433.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-04
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing acrylate aqueous lacquer has problems such as poor leveling performance, low gloss and insufficient wear resistance, which limits its application.

Method used

The hydrosilicon addition reaction of modified nano calcium carbonate and silicone is carried out, and rigid cyclic siloxane and polyether segments are introduced, combined with epoxy ring-opening reaction, forming double bond-containing nano calcium carbonate, which is uniformly dispersed in the modified acrylate emulsion, improving its wear resistance and leveling properties.

Benefits of technology

It significantly improves the leveling, gloss and wear resistance of water-based varnish, and solves the problem of insufficient performance of existing products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of oil polish, in particular to high-leveling water-based oil polish and a preparation process thereof. The high-leveling water-based glazing oil is prepared from the following components in parts by weight: 10 to 25 parts of deionized water, 20 to 45 parts of modified acrylate emulsion, 0.1 to 0.5 part of a defoaming agent, 0.1 to 3 parts of a leveling agent, 0.1 to 2 parts of a wetting agent and 1 to 3 parts of a coalescing agent. The preparation method comprises the following steps: uniformly mixing deionized water and an emulsifier, adding styrene, methyl methacrylate, butyl acrylate, acrylic acid, methacryloyloxymethyl phenyl dimethyl silane and double-bond-containing nano calcium carbonate, uniformly mixing, and carrying out a polymerization reaction under the action of an initiator to prepare a modified acrylate emulsion; and uniformly mixing the modified acrylate emulsion, deionized water, a defoaming agent, a flatting agent, a wetting agent and a coalescing agent, and filtering to prepare the high-leveling water-based oil polish with high glossiness and strong wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glazing oils, in particular to a high-leveling water-based glazing oil and a preparation process thereof. Background Art

[0002] With the improvement of people's living standards and the enhancement of environmental awareness, consumers have higher and higher requirements for product quality and environmental performance. Especially in the printing industry, environmental protection requirements have become a key factor restricting the development of traditional products. Most traditional varnishes are solvent-based, usually with polyurethane, SBS, EVA and other resins as the main resins, ethyl acetate, toluene and other solvents, and tackifying resins, plasticizers and other additives. There are disadvantages of organic solvents being flammable, volatile and polluting the environment. Therefore, non-toxic and pollution-free water-based varnish products are favored by people and can replace existing solvent-based varnish products that pollute the air.

[0003] Water-based varnish refers to a liquid that uses water as a carrier and is applied online with a printing press or offline with a varnishing machine to increase the gloss, water resistance and wear resistance of paper printed products. Depending on the system, water-based varnish can be divided into two types: aqueous solution type and emulsion type. Among them, acrylic emulsion type water-based varnish has the characteristics of good film-forming performance, strong adhesion to the substrate, and not easy to turn yellow or discolor under long-term strong sunlight, and has been widely studied and applied. However, acrylic water-based varnish generally has problems such as poor leveling performance, low gloss, and insufficient wear resistance, which greatly limits its application.

[0004] Therefore, we propose a high-leveling water-based varnish and its preparation process. Summary of the invention

[0005] The purpose of the present invention is to provide a high-leveling water-based varnish and a preparation process to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A preparation process of a high-leveling water-based varnish comprises the following steps: Step S1: Mix two-thirds of deionized water and an emulsifier in parts by weight, add styrene, methyl methacrylate, butyl acrylate, acrylic acid, methacryloyloxymethylphenyldimethylsilane and double-bond nano-calcium carbonate, and mix them evenly to prepare a pre-emulsion; Step S2: uniformly mix the sodium bicarbonate and the remaining mass parts of deionized water, raise the temperature to 80-85° C., drop one-third mass parts of the pre-emulsion and one-third mass parts of the ammonium persulfate aqueous solution, drip for 1.5-2.0 hours, and keep warm for 30-40 minutes; raise the temperature to 85-90° C., drop the remaining mass parts of the pre-emulsion and the remaining mass parts of the ammonium persulfate aqueous solution, drip for 3-4 hours, keep warm for 1-2 hours, cool to room temperature, adjust the pH value to 8-9 with ammonia water, filter, and obtain a modified acrylic emulsion; Step S3: uniformly mixing the modified acrylic ester emulsion, deionized water, defoamer, leveling agent, wetting agent and film-forming aid, and filtering to obtain a high-leveling water-based varnish.

[0007] Furthermore, the high-leveling water-based varnish comprises the following components by weight: 10-25 parts of deionized water, 20-45 parts of modified acrylic emulsion, 0.1-0.5 parts of defoaming agent, 0.1-3 parts of leveling agent, 0.1-2 parts of wetting agent, and 1-3 parts of film-forming aid.

[0008] Furthermore, the modified acrylic emulsion includes the following components by weight: 0.5-1.0 parts of sodium bicarbonate, 90-120 parts of deionized water, 1.0-3.0 parts of emulsifier, 10-15 parts of styrene, 20-25 parts of methyl methacrylate, 30-40 parts of butyl acrylate, 2-4 parts of acrylic acid, 3-5 parts of methacryloyloxymethylphenyldimethylsilane, 5-15 parts of double-bond nano-calcium carbonate, and 15-36 parts of ammonium persulfate aqueous solution.

[0009] Furthermore, the concentration of the ammonium persulfate aqueous solution is 5-10 wt %.

[0010] Furthermore, the preparation method of the double-bond nano calcium carbonate is as follows: Step (1): adding 2,3-epoxypropyltrimethylammonium chloride to deionized water and mixing evenly, adding nano calcium carbonate, ultrasonically dispersing evenly, and ball milling to obtain modified nano calcium carbonate; Step (2): Under nitrogen protection, 1,3,5,7-tetramethylcyclotetrasiloxane, allyloxy polyoxyethylene ether and cardanol are uniformly mixed, the temperature is raised to 90-100° C., chloroplatinic acid-isopropanol solution is added, the reaction is carried out for 8-10 hours, and vacuum distillation is performed to obtain modified silicone; Step (3): uniformly mix the modified organosilicon, maleic anhydride and p-toluenesulfonic acid, react at 60-80° C. for 3-5 hours, and cool to room temperature to obtain an intermediate; Step (4): Under nitrogen protection, the modified nano-calcium carbonate, the intermediate and N,N-dimethylformamide are mixed evenly, tetraethylammonium bromide and hydroquinone are added and mixed evenly, the temperature is raised to 110-120°C, the reaction is performed for 5-7 hours, the mixture is cooled to room temperature, and after washing and drying, nano-calcium carbonate containing double bonds is obtained.

[0011] Furthermore, in the step (1), the mass ratio of nano-calcium carbonate, 2,3-epoxypropyltrimethylammonium chloride and deionized water is 1:(1-3):(40-50).

[0012] Furthermore, in the step (2), the mass ratio of 1,3,5,7-tetramethylcyclotetrasiloxane, allyloxy polyoxyethylene ether and cardanol is 1:(2.0-2.5):(2-4).

[0013] Furthermore, in the step (2), the amount of chloroplatinic acid-isopropanol solution used is 0.0001 mol / L, calculated as platinum atom, and the mass ratio of chloroplatinic acid to isopropanol in the chloroplatinic acid-isopropanol solution is 1:(50-100).

[0014] Furthermore, in step (3), the mass ratio of modified silicone, maleic anhydride and p-toluenesulfonic acid is 1:(1-2):(0.03-0.05).

[0015] Furthermore, in the step (4), the mass ratio of the modified nano-calcium carbonate, the intermediate and N,N-dimethylformamide is 1:(2-4):(20-30).

[0016] Furthermore, the mass ratio of the modified nano-calcium carbonate, tetraethylammonium bromide and hydroquinone is 1: (0.03-0.05): (0.01-0.03).

[0017] Furthermore, the emulsifier is compounded by anionic emulsifier and nonionic emulsifier in a mass ratio of 1:(1-4).

[0018] Furthermore, the anionic emulsifier is one or more of sodium alkylbenzene sulfonate, ammonium alkyl alcohol polyether sulfate, sodium alkyl alcohol ether sulfate, alkyl (aryl) phosphate ester, and fatty alcohol (alkylphenol) polyoxyethylene ether phosphate ester.

[0019] Furthermore, the nonionic emulsifier is one or more of alkyl polyoxyethylene ether, fatty alcohol polyoxyethylene ether, and alkylphenol ethoxylate.

[0020] Furthermore, the film-forming aid is dipropylene glycol butyl ether.

[0021] Compared with the prior art, the present invention has the following beneficial effects: 1. A high-leveling water-based varnish and its preparation process of the present invention, wherein nano-calcium carbonate is modified by 2,3-epoxypropyltrimethylammonium chloride, and the epoxy group at the other end is introduced into the surface of the nano-calcium carbonate through adsorption of the positive charge of the quaternary ammonium salt with the surface of the nano-calcium carbonate, thereby obtaining modified nano-calcium carbonate, reducing the agglomeration phenomenon between calcium carbonate particles, and improving its dispersibility in an organic matrix; Through the hydrosilylation reaction of 1,3,5,7-tetramethylcyclotetrasiloxane, allyloxypolyoxyethylene ether and cardanol, rigid cyclic siloxane, polyether chain segments and rigid benzene rings are introduced, which can effectively improve the leveling and temperature resistance of the varnish and improve its thermal stability; the hydroxyl groups in the modified silicone are carboxylated by maleic anhydride to produce an intermediate containing a double bond; finally, under the catalysis of tetraethylammonium bromide, the epoxy groups on the surface of the modified nano-calcium carbonate react with the carboxyl groups on the intermediate to obtain nano-calcium carbonate containing a double bond; using nano-calcium carbonate containing a double bond as a polymerization monomer, a free radical addition polymerization reaction is carried out with acrylate monomers to achieve uniform dispersion of nano-calcium carbonate in the modified acrylate emulsion, significantly improving its wear resistance and leveling properties.

[0022] 2. A high-leveling water-based varnish and its preparation process of the present invention are prepared by uniformly mixing modified acrylic emulsion, deionized water, defoaming agent, leveling agent, wetting agent and film-forming aid, filtering and having high leveling water-based varnish, which has high leveling property, glossiness and wear resistance. DETAILED DESCRIPTION

[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In this embodiment, the defoaming agent: model is German BYK-022; the leveling agent: model is German BYK-361N; the wetting agent: model is German TEGO-245; nano calcium carbonate: particle size is 20nm, sourced from Shanghai Naio Nano Technology Co., Ltd.; allyloxy polyoxyethylene ether: model is APEG-300, sourced from Jiangsu Hai'an Petrochemical Plant.

[0025] In the following examples and comparative examples, 1 part is equal to 10 g.

[0026] Embodiment 1: A preparation process of a high-leveling water-based varnish, comprising the following processes: Step S1: 60 parts of deionized water and 1.0 part of emulsifier are mixed evenly, and 10 parts of styrene, 20 parts of methyl methacrylate, 30 parts of butyl acrylate, 2 parts of acrylic acid, 3 parts of methacryloyloxymethylphenyldimethylsilane and 5 parts of double-bond nano-calcium carbonate are added and mixed evenly to prepare a pre-emulsion; the emulsifier is prepared by compounding sodium alkylbenzene sulfonate and fatty alcohol polyoxyethylene ether in a mass ratio of 1:1; Step S2: 0.5 parts of sodium bicarbonate and 30 parts of deionized water are mixed evenly, the mixture is heated to 80° C., one-third of the pre-emulsion by mass and 5 parts of a 5wt% aqueous solution of ammonium persulfate are added dropwise, the mixture is dripped over a period of 1.5 hours, and the mixture is kept warm for 30 minutes; the mixture is heated to 85° C., the remaining pre-emulsion by mass and 10 parts of a 5wt% aqueous solution of ammonium persulfate are added dropwise, the mixture is dripped over a period of 3 hours, the mixture is kept warm for 1 hour, the mixture is cooled to room temperature, the pH value is adjusted to 8 with aqueous ammonia, and the mixture is filtered with a 300-mesh filter to obtain a modified acrylic emulsion; Step S3: 20 parts of modified acrylic emulsion, 10 parts of deionized water, 0.1 parts of defoaming agent, 0.1 parts of leveling agent, 0.1 parts of wetting agent and 1 part of film-forming aid are mixed evenly, and filtered through a 300-mesh filter to obtain a high-leveling water-based varnish; The preparation method of double-bond nano calcium carbonate is as follows: Step (1): add 5 parts of 2,3-epoxypropyltrimethylammonium chloride to 200 parts of deionized water and mix evenly, add 5 parts of nano calcium carbonate, disperse evenly by ultrasonication, and perform ball milling to obtain modified nano calcium carbonate; Step (2): Under nitrogen protection, 10 parts of 1,3,5,7-tetramethylcyclotetrasiloxane, 20 parts of allyloxy polyoxyethylene ether and 20 parts of cardanol are mixed evenly, the temperature is raised to 90°C, chloroplatinic acid-isopropanol solution is added, the reaction is carried out for 8 hours, and vacuum distillation is performed to obtain modified silicone; the amount of chloroplatinic acid-isopropanol solution is 0.0001 mol / L based on platinum atoms, and the mass ratio of chloroplatinic acid to isopropanol in the chloroplatinic acid-isopropanol solution is 1:50; Step (3): 10 parts of modified silicone, 10 parts of maleic anhydride and 0.3 parts of p-toluenesulfonic acid were mixed evenly, reacted at 60° C. for 3 hours, and cooled to room temperature to obtain an intermediate; Step (4): Under nitrogen protection, 5 parts of modified nano-calcium carbonate, 10 parts of the intermediate and 100 parts of N,N-dimethylformamide are mixed evenly, 0.15 parts of tetraethylammonium bromide and 0.05 parts of hydroquinone are added and mixed evenly, the mixture is heated to 110°C, reacted for 5 hours, cooled to room temperature, washed and dried to obtain nano-calcium carbonate containing double bonds.

[0027] Embodiment 2: A preparation process of a high-leveling water-based varnish, comprising the following process: Step S1: 70 parts of deionized water and 2.0 parts of emulsifier are mixed evenly, and 12 parts of styrene, 22 parts of methyl methacrylate, 35 parts of butyl acrylate, 3 parts of acrylic acid, 4 parts of methacryloyloxymethylphenyldimethylsilane and 10 parts of double-bond nano-calcium carbonate are added and mixed evenly to prepare a pre-emulsion; the emulsifier is prepared by compounding sodium alkylbenzene sulfonate and fatty alcohol polyoxyethylene ether in a mass ratio of 1:3; Step S2: 0.8 parts of sodium bicarbonate and 35 parts of deionized water are mixed evenly, the mixture is heated to 80° C., one third of the pre-emulsion by mass and 9 parts of an 8wt% aqueous solution of ammonium persulfate are added dropwise, the mixture is dripped over a period of 1.5 hours, and the mixture is kept warm for 30 minutes; the mixture is heated to 85° C., the remaining pre-emulsion by mass and 18 parts of an 8wt% aqueous solution of ammonium persulfate are added dropwise, the mixture is dripped over a period of 3 hours, the mixture is kept warm for 1 hour, the mixture is cooled to room temperature, the pH value is adjusted to 8.5 with aqueous ammonia, and the mixture is filtered with a 300-mesh filter to obtain a modified acrylic emulsion; Step S3: 30 parts of modified acrylic emulsion, 18 parts of deionized water, 0.3 parts of defoamer, 1 part of leveling agent, 1 part of wetting agent and 2 parts of film-forming aid are mixed evenly, and filtered through a 300-mesh filter to obtain a high-leveling water-based varnish; The preparation method of double-bond nano calcium carbonate is as follows: Step (1): adding 20 parts of 2,3-epoxypropyltrimethylammonium chloride to 900 parts of deionized water and mixing evenly, adding 10 parts of nano calcium carbonate, ultrasonically dispersing evenly, and ball milling to obtain modified nano calcium carbonate; Step (2): Under nitrogen protection, 10 parts of 1,3,5,7-tetramethylcyclotetrasiloxane, 22 parts of allyloxy polyoxyethylene ether and 30 parts of cardanol are mixed evenly, the temperature is raised to 95°C, chloroplatinic acid-isopropanol solution is added, the reaction is carried out for 9 hours, and vacuum distillation is performed to obtain modified silicone; the amount of chloroplatinic acid-isopropanol solution is 0.0001 mol / L based on platinum atoms, and the mass ratio of chloroplatinic acid to isopropanol in the chloroplatinic acid-isopropanol solution is 1:80; Step (3): 30 parts of modified silicone, 45 parts of maleic anhydride and 1.2 parts of p-toluenesulfonic acid were mixed evenly, reacted at 70° C. for 4 hours, and cooled to room temperature to obtain an intermediate; Step (4): Under nitrogen protection, 10 parts of modified nano-calcium carbonate, 30 parts of the intermediate and 250 parts of N,N-dimethylformamide are mixed evenly, 0.4 parts of tetraethylammonium bromide and 0.2 parts of hydroquinone are added and mixed evenly, the temperature is raised to 115°C, the reaction is carried out for 6 hours, the mixture is cooled to room temperature, and after washing and drying, nano-calcium carbonate containing double bonds is obtained.

[0028] Embodiment 3: A preparation process of a high-leveling water-based varnish, comprising the following processes: Step S1: 80 parts of deionized water and 3.0 parts of emulsifier are mixed evenly, and 15 parts of styrene, 25 parts of methyl methacrylate, 40 parts of butyl acrylate, 4 parts of acrylic acid, 5 parts of methacryloyloxymethylphenyldimethylsilane and 15 parts of double-bond nano-calcium carbonate are added and mixed evenly to prepare a pre-emulsion; the emulsifier is prepared by compounding sodium alkylbenzene sulfonate and fatty alcohol polyoxyethylene ether in a mass ratio of 1:4; Step S2: 1.0 part of sodium bicarbonate and 40 parts of deionized water are mixed evenly, the temperature is raised to 80° C., one-third of the pre-emulsion by mass and 12 parts of a 10 wt% ammonium persulfate aqueous solution are added dropwise, the dripping is completed in 1.5 hours, and the temperature is kept for 30 minutes; the temperature is raised to 85° C., the remaining pre-emulsion by mass and 24 parts of a 10 wt% ammonium persulfate aqueous solution are added dropwise, the dripping is completed in 3 hours, the temperature is kept for 1 hour, the mixture is cooled to room temperature, the pH value is adjusted to 9 with aqueous ammonia, and the mixture is filtered with a 300-mesh filter to obtain a modified acrylic emulsion; Step S3: 45 parts of modified acrylic emulsion, 25 parts of deionized water, 0.5 parts of defoamer, 3 parts of leveling agent, 2 parts of wetting agent and 3 parts of film-forming aid are mixed evenly, and filtered through a 300-mesh filter to obtain a high-leveling water-based varnish; The preparation method of double-bond nano calcium carbonate is as follows: Step (1): adding 45 parts of 2,3-epoxypropyltrimethylammonium chloride to 2250 parts of deionized water and mixing evenly, adding 15 parts of nano calcium carbonate, ultrasonically dispersing evenly, and ball milling to obtain modified nano calcium carbonate; Step (2): Under nitrogen protection, 10 parts of 1,3,5,7-tetramethylcyclotetrasiloxane, 25 parts of allyloxy polyoxyethylene ether and 40 parts of cardanol are mixed evenly, the temperature is raised to 100°C, chloroplatinic acid-isopropanol solution is added, the reaction is carried out for 10 hours, and vacuum distillation is performed to obtain modified silicone; the amount of chloroplatinic acid-isopropanol solution is 0.0001 mol / L based on platinum atoms, and the mass ratio of chloroplatinic acid to isopropanol in the chloroplatinic acid-isopropanol solution is 1:100; Step (3): 60 parts of modified silicone, 120 parts of maleic anhydride and 3 parts of p-toluenesulfonic acid were mixed evenly, reacted at 80° C. for 5 hours, and cooled to room temperature to obtain an intermediate; Step (4): Under nitrogen protection, 15 parts of modified nano-calcium carbonate, 60 parts of the intermediate and 450 parts of N,N-dimethylformamide are mixed evenly, 0.75 parts of tetraethylammonium bromide and 0.45 parts of hydroquinone are added and mixed evenly, the temperature is raised to 120°C, the reaction is carried out for 7 hours, the mixture is cooled to room temperature, and after washing and drying, nano-calcium carbonate containing double bonds is obtained.

[0029] Comparative Example 1: The modified acrylic emulsion includes the following components by weight: 0.8 parts of sodium bicarbonate, 105 parts of deionized water, 2 parts of emulsifier, 12 parts of styrene, 22 parts of methyl methacrylate, 35 parts of butyl acrylate, 3 parts of acrylic acid, 4 parts of methacryloyloxymethylphenyldimethylsilane, and 27 parts of ammonium persulfate aqueous solution; compared with Example 2, no double-bonded nano-calcium carbonate is added to the modified acrylic emulsion of Comparative Example 2, and other steps and processes are the same as those of Example 2.

[0030] Comparative Example 2: The modified acrylic latex includes the following components by weight: 0.8 parts of sodium bicarbonate, 105 parts of deionized water, 2 parts of emulsifier, 12 parts of styrene, 22 parts of methyl methacrylate, 35 parts of butyl acrylate, 3 parts of acrylic acid, 4 parts of methacryloyloxymethylphenyldimethylsilane, 10 parts of nano-calcium carbonate, and 27 parts of ammonium persulfate aqueous solution; compared with Example 2, Comparative Example 2 replaces the double-bond nano-calcium carbonate with ordinary nano-calcium carbonate of the same mass, and the other steps and processes are the same as Example 2.

[0031] Comparative Example 3: A preparation process of a high-leveling water-based varnish, comprising the following processes: The preparation method of double-bond nano calcium carbonate is as follows: Step (1): adding 20 parts of 2,3-epoxypropyltrimethylammonium chloride to 900 parts of deionized water and mixing evenly, adding 10 parts of nano calcium carbonate, ultrasonically dispersing evenly, and ball milling to obtain modified nano calcium carbonate; Step (2): Under nitrogen protection, 10 parts of 1,3,5,7-tetramethylcyclotetrasiloxane and 30 parts of cardanol are mixed evenly, the temperature is raised to 95°C, chloroplatinic acid-isopropanol solution is added, the reaction is carried out for 9 hours, and vacuum distillation is performed to obtain modified silicone; the amount of chloroplatinic acid-isopropanol solution is 0.0001 mol / L based on platinum atoms, and the mass ratio of chloroplatinic acid to isopropanol in the chloroplatinic acid-isopropanol solution is 1:80; Step (3): 30 parts of modified silicone, 45 parts of maleic anhydride and 1.2 parts of p-toluenesulfonic acid were mixed evenly, reacted at 70° C. for 4 hours, and cooled to room temperature to obtain an intermediate; Step (4): Under nitrogen protection, 10 parts of modified nano-calcium carbonate, 5 parts of the intermediate and 250 parts of N,N-dimethylformamide are mixed evenly, 0.4 parts of tetraethylammonium bromide and 0.2 parts of hydroquinone are added and mixed evenly, the mixture is heated to 115°C, reacted for 6 hours, cooled to room temperature, washed and dried, and then nano-calcium carbonate containing double bonds is obtained; Compared with Example 2, in step (2) of Comparative Example 3, the mass ratio of 1,3,5,7-tetramethylcyclotetrasiloxane, allyloxypolyoxyethylene ether and cardanol is 1:1:1, and the other steps are the same as those in Example 2.

[0032] Experiment: Take the high-leveling water-based varnish obtained in Examples 1-3 and Comparative Examples 1-3 to prepare samples, test their properties respectively and record the test results: Gloss test: Apply water-based varnish on white cardboard, wait for it to be completely dry, and then use WGG60 gloss meter to measure the gloss; Abrasion resistance test: Apply water-based varnish evenly on the surface of black cardboard, wait for it to be completely dry, and then use BGD630 ink friction resistance tester to measure according to GB / T 7706-2008 standard, and record the number of abrasion times; Leveling performance test: Test the leveling performance of varnish according to JB / T 3998-1999.

[0033] The test results are as follows:

[0034] According to the data in the above table, we can clearly draw the following conclusions: 1. Compared with Examples 1-3, the glossiness of the product obtained in Comparative Example 1 is improved, but the abrasion resistance and leveling properties are reduced, indicating that the addition of double-bonded nano-calcium carbonate in the present invention can improve the abrasion resistance while maintaining the relative stability of the glossiness, thereby taking into account both the gloss and abrasion resistance of the coating film.

[0035] 2. Compared with Examples 1-3, the gloss, abrasion resistance and leveling properties of the product obtained in Comparative Example 2 are all reduced. It can be seen that compared with ordinary nano-calcium carbonate, the present invention significantly improves the dispersibility and compatibility of modified nano-calcium carbonate by introducing structures such as quaternary ammonium salts, polyether segments and rigid benzene rings on the surface of nano-calcium carbonate, so that the coating film has better leveling, abrasion resistance and gloss.

[0036] 3. Compared with Examples 1-3, the wear resistance and leveling properties of the product obtained in Comparative Example 3 are both reduced, which indicates that when the addition amount of allyloxypolyoxyethylene ether and cardanol is reduced, the dispersibility and stability of the material will decrease. It can be seen that the performance of the double-bond nano-calcium carbonate prepared by the present invention is affected by the ratio of each reagent in its preparation process. By selecting the mass ratio within the range, the prepared double-bond nano-calcium carbonate has excellent dispersibility, thereby improving the leveling property of the glazing oil.

[0037] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A preparation process of a high-leveling water-based varnish, characterized in that: The steps include: Step S1: Mix two-thirds of deionized water and an emulsifier in parts by weight, add styrene, methyl methacrylate, butyl acrylate, acrylic acid, methacryloyloxymethylphenyldimethylsilane and double-bond nano-calcium carbonate, and mix them evenly to prepare a pre-emulsion; Step S2: uniformly mix the sodium bicarbonate and the remaining mass parts of deionized water, raise the temperature to 80-85° C., drop one-third mass parts of the pre-emulsion and one-third mass parts of the ammonium persulfate aqueous solution, drip for 1.5-2.0 hours, and keep warm for 30-40 minutes; raise the temperature to 85-90° C., drop the remaining mass parts of the pre-emulsion and the remaining mass parts of the ammonium persulfate aqueous solution, drip for 3-4 hours, keep warm for 1-2 hours, cool to room temperature, adjust the pH value to 8-9 with ammonia water, filter, and obtain a modified acrylic emulsion; Step S3: uniformly mixing the modified acrylic ester emulsion, deionized water, defoamer, leveling agent, wetting agent and film-forming aid, and filtering to obtain a high-leveling water-based varnish.

2. The preparation process of a high-leveling water-based varnish according to claim 1, characterized in that: The high-leveling water-based varnish comprises the following components by weight: 10-25 parts of deionized water, 20-45 parts of modified acrylic ester emulsion, 0.1-0.5 parts of defoaming agent, 0.1-3 parts of leveling agent, 0.1-2 parts of wetting agent and 1-3 parts of film-forming aid.

3. The preparation process of a high-leveling water-based varnish according to claim 2, characterized in that: The modified acrylic emulsion comprises the following components by weight: 0.5-1.0 parts of sodium bicarbonate, 90-120 parts of deionized water, 1.0-3.0 parts of emulsifier, 10-15 parts of styrene, 20-25 parts of methyl methacrylate, 30-40 parts of butyl acrylate, 2-4 parts of acrylic acid, 3-5 parts of methacryloyloxymethylphenyldimethylsilane, 5-15 parts of double-bond nano calcium carbonate, and 15-36 parts of ammonium persulfate aqueous solution.

4. The process for preparing a high-leveling water-based varnish according to claim 2, characterized in that: The preparation method of the double-bond nano calcium carbonate is as follows: Step (1): adding 2,3-epoxypropyltrimethylammonium chloride to deionized water and mixing evenly, adding nano calcium carbonate, ultrasonically dispersing evenly, and ball milling to obtain modified nano calcium carbonate; Step (2): Under nitrogen protection, 1,3,5,7-tetramethylcyclotetrasiloxane, allyloxy polyoxyethylene ether and cardanol are uniformly mixed, the temperature is raised to 90-100° C., chloroplatinic acid-isopropanol solution is added, the reaction is carried out for 8-10 hours, and vacuum distillation is performed to obtain modified silicone; Step (3): uniformly mix the modified organosilicon, maleic anhydride and p-toluenesulfonic acid, react at 60-80° C. for 3-5 hours, and cool to room temperature to obtain an intermediate; Step (4): Under nitrogen protection, the modified nano-calcium carbonate, the intermediate and N,N-dimethylformamide are mixed evenly, tetraethylammonium bromide and hydroquinone are added and mixed evenly, the temperature is raised to 110-120°C, the reaction is performed for 5-7 hours, the mixture is cooled to room temperature, and after washing and drying, nano-calcium carbonate containing double bonds is obtained.

5. The process for preparing a high-leveling water-based varnish according to claim 4, characterized in that: In the step (1), the mass ratio of nano calcium carbonate, 2,3-epoxypropyltrimethylammonium chloride and deionized water is 1:(1-3):(40-50).

6. The process for preparing a high-leveling water-based varnish according to claim 4, characterized in that: In the step (2), the mass ratio of 1,3,5,7-tetramethylcyclotetrasiloxane, allyloxy polyoxyethylene ether and cardanol is 1:(2.0-2.5):(2-4).

7. The process for preparing a high-leveling water-based varnish according to claim 4, characterized in that: In the step (4), the mass ratio of modified nano-calcium carbonate, intermediate, tetraethylammonium bromide and hydroquinone is 1:(2-4):(0.03-0.05):(0.01-0.03).

8. The process for preparing a high-leveling water-based varnish according to claim 3, characterized in that: The concentration of the ammonium persulfate aqueous solution is 5-10 wt %.

9. The process for preparing a high-leveling water-based varnish according to claim 3, characterized in that: The emulsifier is prepared by compounding an anionic emulsifier and a nonionic emulsifier in a mass ratio of 1:(1-4).

10. A high-leveling water-based varnish prepared according to the preparation process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Shape-controlled nano calcium carbonate powder modified by cardanol polyoxyethylene ether composite treatment agent and preparation method of shape-controlled nano calcium carbonate powder

    CN106700656A

  • Preparation method of high-gloss water-based glazing oil for grainy paper

    CN114316124A

  • Temperature-resistant water-based glazing oil for printing and preparation method of temperature-resistant water-based glazing oil

    CN114481688A

  • High-temperature-resistant mixed silicone rubber and preparation method thereof

    CN116875064A

  • High-leveling-property ink fountain water-based oil polish and preparation method thereof

    CN117430997A